Maternal and Neonatal Outcomes of Pregnancy with Preterm Premature Rupture of Membranes - Aliya Hafeez, Shazia Ashraf, Afshan Batool, Qurat-Ul-Ain, Zain-Ul-Abideen (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Preterm premature rupture of membranes is a critical condition which can lead to negative maternal and fetal outcomes. Objective: To assess the maternal and neonatal outcomes of preterm premature rupture of membranes in pregnant women. Study Design: Retrospective study. Place and Duration of Study: Department of Gynaecology & Obstetrics, Shifa International Hospital, Faisalabad from 1st March 2023 to 31st July 2023. Methodology: Ninety pregnant women who suffered from preterm premature rupture of membranes were enrolled. A complete detail of their medical record until delivery and neonatal outcomes were studied and analyzed. All those women’s records having preterm premature rupture of membranes (between 24 weeks to 36 weeks) were included in this study. The age of pregnant women included was within 18-45 years. The negative outcomes of the preterm premature rupture of membranes in maternal and neonates were recorded. Results: The mean age of the pregnant women was 27.5±3.9 years with the mean gestational age as 31.2±3.3 weeks at the time of membrane rupture. Around 42% of the pregnant women were primigravida with majority having a normal body mass index (24.9±3.5 kg/m2). About 17.7% of the women suffered from chorioamnionitis followed by 7.7% suffering from endometritis and 6.6% with wound infection. There were 5.5% women having placental abruption while 2.2% has sepsis developed in them. The neonatal outcomes presented a mean birth weight value as 1841±426 grams of neonates with low birth weight observed in 48.8% neonates. The Apgar score <7 at 5 min, was observed in 15.5%. There were 60% neonates who were initially admitted in the NICU with a mean NICU stay as 12.2±6.8 days. Conclusion: Preterm Premature rupture of membranes is significantly associated with preterm gestational age and negative outcomes of maternal and neonatal health including, Sepsis, chorioamnionitis, placental abruption, wound infection as well as low birth weight, sepsis, respiratory distress and morbidity in the neonates respectively. Keywords: Maternal, Fetal outcome, Pregnancy, Preterm premature rupture